Laparoscopic greater curvature plication (LGCP) for treatment of morbid obesity in a series of 244 patients - Fried, M; Dolezalova, K; Buchwald, J N; McGlennon, T W; Sramkova, P; Ribaric, G (Obesity surgery, 2012)
BACKGROUND: Laparoscopic greater curvature plication (LGCP) is a new metabolic/bariatric surgical procedure that requires no resection, bypass, or implantable device. We report LGCP outcomes in 244 morbidly obese patients. METHODS: Between 2010 and 2011, patients underwent LGCP. Body mass index (BMI, kilogram per square meter) evolution, excess BMI loss (%EBMIL), excess weight loss (%EWL), complications, and type 2 diabetes mellitus (T2DM) changes were recorded. Repeated-measures analysis of variance (ANOVA) was used to assess weight change at 6, 12, and 18 months. Subgroup analyses were conducted to provide benchmark outcomes at 6 months. Logistic regression was used to identify characteristics predictive of suboptimal weight loss. RESULTS: Mean baseline BMI (±SD) was 41.4 ± 5.5 (80.7 % women, mean age 46.1 ± 11.0 years, 68 [27.9 %] patients had T2DM). Mean operative time was 70.6 min; mean hospitalization, 36 h (24-72). Sixty-eight patients (27.9 %) experienced postoperative nausea and/or vomiting that was controlled within 36 h. There was no mortality. Major complication rate was 1.2 % (n = 3). Repeated-measures ANOVA indicated significant weight loss across time points (p < 0.001). At 6 months (n = 105), BMI, %EBMIL, and %EWL were 36.1 ± 4.7, 34.8 ± 17.3, and 31.8 ± 15.9. Preoperative BMI was the only predictor of weight loss. Patients with BMI <40 lost more weight than those ≥40, although by 9 months, differences were no longer significant. In patients with preoperative BMI <40, 18-month %EWL approached 50 % and %EBMIL exceeded 50 %. At 6 months, 96.9 % of patients' T2DM was significantly improved/resolved. CONCLUSIONS: Over the short term, LGCP results in effective weight loss and significant T2DM reduction with a very low rate of complications.
Keywords: Gastroplasty; logistické modely; hmotnostní úbytek; Humans; laparoskopie; index tělesné hmotnosti; lidé středního věku; Body Mass Index; Female; analýza rozptylu; Analysis of Variance; výsledek terapie; lidé; Diabetes Mellitus, Type 2; Obesity, Morbid; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; morbidní obezita; Weight Loss; Treatment Outcome; Laparoscopy; mužské pohlaví; prospektivní studie; diabetes mellitus 2. typu; Logistic Models; následné studie; gastroplastika; Prospective Studies